Analisis kesulitan siswa dalam memecahkan masalah matematis menyelesaikan soal pada materi bangun ruang sisi datar selama pembelajaran jarak jauh (PJJ) pada masa pasca pandemi - Nafi, Nafiatuz Zuliah; Murtianto, Yanuar Hery; Kartinah, Kartinah (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The Covid-19 pandemic is currently sweeping the world, especially in Indonesia. The learning system faces situations that require teachers to be able to master distance learning media. Conventional classes had to be moved to virtual ones where students and educators were asked to study from home as a preventive measure in breaking the spread of the COVID-19 chain (Basilaia dan Kvavadze 2020). However, students experience difficulties in one of the subjects, namely mathematics, especially students’ mathematical problem solving abilities during distance learning which affects students’ difficulties in solving math problems on flat-sided geometry. This study aims to describe the students’ mathematical problem solving ability and the difficulty of solving students’ problems in learning mathematics during distance learning. This study uses descriptive qualitative research methods. The subjects in this study were students of class VIII A of SMP Negeri 1 Karangawen Demak in the academic year 2020-2021 and the object of research was the students’ mathematical problem solving ability and the difficulty of solving students’ problems in mathematics learning during distance learning. Data collection techniques using written tests and interviews. The data analysis technique used by class VIII A students of SMPN 1 Karangawen Demak, totaling 30 students and the results obtained were: 13 students with high scores, 12 students with moderate scores, and 5 students with low scores, then 3 students were selected as subjects have 1 high math ability, 1 medium math ability, and 1 low math ability.